1993
DOI: 10.1159/000236505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lodoxamide on in vitro and in vivo Conjunctival Immediate Hypersensitivity Responses in Rats

Abstract: The antiallergic compound, lodoxamide, was evaluated for its abilities to attenuate a local allergic reaction in rat conjunctiva in vivo and to inhibit rat conjunctival mast cell mediator release in vitro. Topically applied lodoxamide (0.01, 0.10 and 1.0%, w/v) dose-dependently reduced the allergic response (23, 43 and 72%, respectively) in vivo. Lodoxamide was more effective than cromolyn sodium, N-acetyl aspartyl glutamic acid (Naaxia®) and levocabastine, and 25 (7–200) times more potent than nedocromil sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Güler et al [14]found lodoxamide more effective compared with sodium cromoglycate in the inhibition of vascular permeability in a passive allergy model of rabbits. Our study is in accordance with these two studies except for the level of efficacy of levacobastine reported in the first study [11]. That study differs with regard to the model tested.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Güler et al [14]found lodoxamide more effective compared with sodium cromoglycate in the inhibition of vascular permeability in a passive allergy model of rabbits. Our study is in accordance with these two studies except for the level of efficacy of levacobastine reported in the first study [11]. That study differs with regard to the model tested.…”
Section: Discussionsupporting
confidence: 93%
“…This is why most of the studies evaluating the effectiveness of various substances on type I allergic reactions are focused on mast cells [6, 8, 9, 11]. Mast cells have been identified and described in the normal conjunctiva of rats and humans [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4A, n = 4 experiments). Since lodoxamide is able to inhibit the release of rat mast cell mediators in vitro and in vivo [15, 16], and since rat mast cell-eosinophil interactions are required to induce antibody-dependent cell-mediated cytotoxicity [13], we have also investigated the role of lodoxamide in rat eosinophil-mediated antibody-dependent cell-mediated cytotoxicity. The results presented in figure 4B clearly indicate a dose-dependent inhibition of cytotoxicity, reaching more than 90% inhibition for the highest concentration of lodoxamide (p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…IgE-mediated models of rat conjunctivitis used either direct or indirect sensitization and a large number of questions were answered with this species. Using ovalbumin-based protocols, it was shown that the rat models of allergic eye disease exhibit similar pharmacological properties as guinea-pig models concerning the effects of drugs such as lodoxamide, nedocromil, sodium cromoglycate, levacobastine, cimetidine, diclofenac sodium: (65, 72), or lodoxamide (73).…”
Section: Ratsmentioning
confidence: 99%